Breast Cancer Incidence in 2, 305, 427 Screened Asymptomatic Women: Long-Term Outcomes During Menopause [307]. (May 2015) - Cutler, Winnifred; Burki, Regula E.; Kolter, James S.; Chambliss, Catherine; Friedmann, Erika
Abstract : INTRODUCTION: Breast cancer, screening mammography, and mortality reduction studies generally have not asked: What percentage of asymptomatic peri- and postmenopausal women will be diagnosed with a first invasive breast cancer over their next 25 years? What percentage remain cancer-free? METHODS: We systematically searched for all published breast cancer screening studies that met five criteria: breast cancer-free history at enrollment, number enrolled specified, number diagnosed shown, each woman counted only once, and length of follow-up stated. Linear regression was used to quantify relationships between incidence and length of follow-up in the 19 studies located (2, 305, 427 peri- and postmenopausal women). This rigorous method avoided less rigorous meta-analyses that obscure heterogeneity by pooling data. RESULTS: We found significant linear relationships between incidence and duration: 1) average cumulative incidence rate of first case of invasive breast cancer increased by 0.20% each year when all 19 studies were considered (95% confidence interval [CI] 0.17–0.23%; P< .01; R 2 =0.90). With 25 years of follow-up, 94.55% remained disease-free (95% CI 93.97– 95.13). 2) In 12 studies (n=1, 711, 178) that enrolled only postmenopausal women, on average 0.23% of women were diagnosed with a first case of invasive breast cancer each year (95% CI 0.18–0.28%; P< .01, R 2 =0.88). CONCLUSION: Most (approximately 95%) screened asymptomatic peri- and postmenopausal women remained breast cancer-free throughout 25 years of follow-up. Women accepting clinical examinations without mammograms would experience even higher cancer-free rates because innocuous positives (comprising 30–50% of mammography diagnoses) would be undetected. Informed consent to asymptomatic women should include these results in health care planning.